2022
DOI: 10.1017/s1366728921001012
|View full text |Cite
|
Sign up to set email alerts
|

Decision-making depends on language: A meta-analysis of the Foreign Language Effect

Abstract: In the present meta-analysis, we investigated the robustness and the magnitude of the Foreign Language Effect (FLE) – that is, the putative effect of language context (native versus foreign language) on decision-making. We also investigated whether the FLE is moderated by language experience – measured by second language age of acquisition and proficiency – or by methodological choices – the types of decision problems adopted, the presentation modality of the tasks administered, and the perspective in which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 59 publications
1
44
0
Order By: Relevance
“…The inconsistency of the above findings has inspired increasing interest in understanding the psychological and linguistic factors contributing to the FLE. A recent meta-analysis (Del Maschio et al, 2022) investigated the magnitude of the FLE on decision-making under conditions of risk (i.e., risk-aversion domain) and moral conflict (i.e., deontological/utilitarian dichotomy), and explored the potential effect of moderating variables related to second language experience (i.e., FL Age of Acquisition [AoA], FL proficiency) and experimental design (i.e., Problem type, Personal force, Task modality). Although the study reported a reliable FLE on decision outcomes, it was not able to detect a contribution of moderator variables on the observed effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inconsistency of the above findings has inspired increasing interest in understanding the psychological and linguistic factors contributing to the FLE. A recent meta-analysis (Del Maschio et al, 2022) investigated the magnitude of the FLE on decision-making under conditions of risk (i.e., risk-aversion domain) and moral conflict (i.e., deontological/utilitarian dichotomy), and explored the potential effect of moderating variables related to second language experience (i.e., FL Age of Acquisition [AoA], FL proficiency) and experimental design (i.e., Problem type, Personal force, Task modality). Although the study reported a reliable FLE on decision outcomes, it was not able to detect a contribution of moderator variables on the observed effect.…”
Section: Introductionmentioning
confidence: 99%
“…Interindividual variability along these dimensions is known to affect bilingual language processing (e.g., Fricke et al, 2019; Sulpizio et al, 2020), and may therefore underlie processing differences in decision-making when using a FL, with potential repercussions on the scope and characteristics of the MFLE. Research has begun to explore the putative influence of linguistic variables such as AoA, proficiency, and language dominance or use on bilinguals’ patterns of moral responding, though with mixed or inconclusive results (see Del Maschio et al, 2022; Stankovic et al, 2022). Yet the role of these variables in modulating bilinguals’ moral reasoning has been emphasized – albeit to varying degrees – by all previous theoretical accounts of the FLE, as detailed in the rest of this section.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of the "reduced emotionality hypothesis", the efficiency of a motivational quote may be reduced if it is presented in an FL rather than an NL because their affective essence is processed differently. Of note, motivational quotes are positive emotion-laden sentences, which contrasts with the fact that most previous FLe literature has used linguistic material that elicits negative affect (see Del Maschio et al's (2022) and Circi et al's (2021) recent meta-analyses). However, in line with the results by Hadjichristidis et al (2019) with positive superstitions, for which they found similar FLe compared to negative superstitions, we expect to find the abovementioned reduction on the efficiency of motivational quotes.…”
Section: Introductionmentioning
confidence: 94%
“…Research has shown that foreign language (FL) use influences judgment and reasoning. This phenomenon, known as the "foreign language effect" (FLe), has been studied exhaustively in the context of moral decision-making and gambling (see Del Maschio, Crespi, Peressotti, Abutalebi & Sulpizio 2022;and Circi, Gatti, Russo & Vecchi 2021), for meta-analyses evidencing the robustness of FLe in these contexts). Compared to the use of one's native language (NL), the use of an FL increases utilitarian behaviour when making moral decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it cannot be ruled out that individual differences in the participants' L2 reading proficiency may have influenced the results. For example, a recent meta-analysis (Stankovic et al, 2022) revealed that lower L2 reading proficiency was associated with more utilitarian judgements in emotionally charged moral dilemmas (but see Circi et al, 2021;Del Maschio et al, 2022). In order to advance research in the filed forward and to attain a better understanding of the MFLe, future studies should attempt to identify potentially relevant variables (such as emotional acculturation, linguistic distance between the L1 and the L2, and L2 reading abilities) and to explore how they contribute to bilinguals' moral choices.…”
Section: Limitations and Future Researchmentioning
confidence: 99%